2013
DOI: 10.1001/jamaneurol.2013.3258
|View full text |Cite
|
Sign up to set email alerts
|

Salience Network Resting-State Activity

Abstract: dvances in functional neuroimaging have provided a window into the brain's intrinsic connectivity, leading to the discovery of the salience network (SLN), composed of the anterior cingulate, insula, striatum, and amygdala. The SLN is activated in healthy patients during tasks requiring attentional selection, task switching, and self-regulation of behavior 1 and is an important neural substrate in frontotemporal dementia (FTD), 2 with dysfunction confirmed on histopathology 3 and resting-state functional magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…Our data indicated that ME/CFS patients had significantly reduced FC between ACC and right insula. Such reduced resting-state connectivity between these regions has been associated with neuropsychological deficits [29 and 30], similar to those seen in patients with ME/CFS. Furthermore, ME/CFS patients in the present study showed increased connectivity between the ACC and hippocampus/PCC.…”
Section: Discussionmentioning
confidence: 89%
“…Our data indicated that ME/CFS patients had significantly reduced FC between ACC and right insula. Such reduced resting-state connectivity between these regions has been associated with neuropsychological deficits [29 and 30], similar to those seen in patients with ME/CFS. Furthermore, ME/CFS patients in the present study showed increased connectivity between the ACC and hippocampus/PCC.…”
Section: Discussionmentioning
confidence: 89%
“…Following previous reports [49][50][51][52], during a 10-min fMRI session, participants were instructed not to think about anything in particular, to keep their eyes closed, and avoid moving and falling asleep. We chose the closed-eyes modality to avoid highly noisy signals coming from the visual cortex [53] and to facilitate attention during interoceptive processing [54,55].…”
Section: (C) Image Analysis (I) Image Acquisitionmentioning
confidence: 99%
“…These authors therefore specifically relate the VENs, not just to the areas wherein they are frequent observed, but to awareness. Such ability for “insight” is greatly reduced in patients affected by autism (Ben Shalom et al, 2006) and frontotemporal dementia (Day et al, 2013). On the other hand, an hyperconnectivity in the salience network (SN), involving the AI, has been observed in children with autism spectrum disorder (Uddin et al, 2013).…”
Section: Functional Connectivity Of the Areas Containing High Densitimentioning
confidence: 99%